Object-oriented design with UML and Java - Barclay, Kenneth A., 1947- (Elsevier Butterworth-Heinemann, 2004)
Unified Modeling Language (UML) is a general-purpose programming language for specifying and visualizing complex software, especially large, object-oriented projects. Object-oriented programming is when a programmer defines not only the data type of a data structure, but also the types of operations/functions that can be applied to the data structure. Java is a general purpose programming language with a number of features that make the language well suited for use on the World Wide Web. Fully road tested from the authors own courses, Object-Oriented Design with UML and Java shows how consider.